A Novel Segment-Based Model for Non-Stationary Vehicle-to-Vehicle Channels With Velocity Variations - Weidong Li; Xiaomin Chen; Qiuming Zhu; Weizhi Zhong; Dazhuan Xu; Fei Bai (IEEE Access, 2019)
By considering the velocity variations of both terminals and moving scatterers, a general segment-based model for non-stationary vehicle-to-vehicle (V2V) channels is proposed in this paper. The time evolving channel parameters, i.e., Doppler frequencies, angles of arrival and departure, path delays, and path powers, are analyzed and simplified by the Taylor series expansions. The proposed model can be applied for realistic V2V communication environments and explicitly reveal the impact of velocity variations on the channels. In addition, the theoretical statistical properties, i.e., the temporal correlation function (TCF), Doppler power spectrum density (DPSD), level-crossing rate (LCR), and average fading duration (AFD) are also analyzed and derived. Simulation results under four typical V2V scenarios show that the theoretical results agree well with the simulated and measured ones, which verifies the effectiveness of both the proposed model and the derivations.